Structural Equation Modeling (SEM) of Performance Evaluation Indexes of Judo & Kurash Federation of the Islamic Republic of Iran - Azam Abdollahi (Journal of Global Pharma Technology, 2017)
This study sought to model the structural equation of performance evaluation of Judo and Kurash Federation of the Islamic Republic of Iran using the BSC approach.This was a descriptive and field-based research. The statistical population consisted of the members, managers, referees, veterans, and experts of the Judo and Kurash Federation of the Islamic Republic of Iran. Purposive sampling technique was used to select the study sample.To collect data, a researcher-made questionnaire was used. The content validity of the questionnaire wasapproved by experts. The reliability was calculated as 0.96 running Cronbach's alpha coefficient. In order to analysethe data and model the structural equation, PLS software was applied. Performance evaluation model of Judo and Kurash Federation of the Islamic Republic of Iran had four factors, 10 dimensions and40indicators, in a way, learning and development factor had 3dimensions and17indicators, internal processes had 3dimensions and 11 indicators, financial factor had 1 dimension and4indicators and customer and sport results had 3dimensions and7indicators. Internal operating processes, customer and sporting results, learning and development and finance were the most important factors, respectively.According to the results, to evaluate their performance, Judo and Kurash Federation of the Islamic Republic of Iran should consider four perspectives of BSC because these dimensions have cause and effect relationship with each other. Also, the federation should consider the dimensions and examined indexes of the current study if it seeks to plan and manage performance evaluation in order to provide the required backgrounds for development.Keywords: Performance Evaluation, Judo and Kurash Federation, balanced scorecard.